Working Capital Efficiency, Cost Control, and Liquidity as Drivers of Profitability: Evidence From Property and Real Estate Companies - Muhammad Syahwildan; Erina Rulianti; Destriani Safitri Efendi (Majapahit Journal of Islamic Finance and Management, 2025)
Real estate companies are required to improve efficiency in financial management to remain competitive and survive in dynamic market conditions. The efficiency of working capital utilization, the effectiveness of cost control, and the level of liquidity are important factors that play a role in determining the company’s profitability level. The sampling method used is non-probability sampling, specifically the purposive sampling method. The sample for this study consists of 8 property and real estate companies listed on the IDX during the 2019-2024 period. This research utilizes EViews 13 for analysis. The research findings indicate that working capital utilization has no effect on profitability.